2019
DOI: 10.2169/internalmedicine.3111-19
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pleural Melanoma: A Case Report and Literature Review

Abstract: Primary pleural melanoma is an extremely rare neoplasm, and to the best of our knowledge, there have been only 8 case reports of this condition in the English literature. We herein report a rare case in which the cytological and immunocytochemical analyses of pleural fluid and ultrasonography (US)-guided biopsy of a pleural lesion were useful for the diagnosis primary pleural melanoma. This case highlights the importance of careful physical examinations, cytomorphologic and immunocytochemical analyses of pleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Hydrocephalus has also been reported as spinal cord lesions that can disturb the cerebrospinal fluid circulation [ 18 ]. In the case of pleural melanomas, the main symptoms include dyspnea, chest pain, and cough [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocephalus has also been reported as spinal cord lesions that can disturb the cerebrospinal fluid circulation [ 18 ]. In the case of pleural melanomas, the main symptoms include dyspnea, chest pain, and cough [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase of FDG uptake is mild and in pleural benign diseases with SUV approximately equal to 1. FDG may be also used to help localize the site for biopsy and improve accuracy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 14,16 which specifically looked at patients with metastatic melanoma and intrathoracic metastases found between 15% and 16% had pleural effusions but did not report on pleural fluid characteristics or clinical significance of the effusion. The majority of the remaining literature includes case reports of unusual presentations, 17,18 black effusions caused by melanoma 19,20,31–36 or primary pleural melanoma 37–40 . While there have been many case reports of black pleural effusions secondary to melanoma, the true prevalence of this rare entity remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the remaining literature includes case reports of unusual presentations, 17,18 black effusions caused by melanoma 19,20,[31][32][33][34][35][36] or primary pleural melanoma. [37][38][39][40] While there have been many case reports of black pleural effusions secondary to melanoma, the true prevalence of this rare entity remains unclear. In our study, we reported 1 case of the 27 effusions which may estimate the prevalence to be around 4%.…”
Section: Discussionmentioning
confidence: 99%